Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago - Last, Peter R.; Manjaji, B. Mabel; Yearsley, Gordon K. (Zootaxa, 2005)
A new stingray, Pastinachus solocirostris sp. nov., is described from material collected from Malaysian Borneo and Indonesia. It differs from the only other recognised member of the genus, P. sephen, in having a smaller adult size, more elongate disc and head, longer and more acute snout covered to its apex with enlarged denticles, more posteriorly located sting, longer and more slender ventral cutaneous fold, enlarged pearl-shaped nuchal thorns, and fewer pectoral-fin radials and vertebrae. It appears to occur primarily in estuaries and turbid coastal marine habitats off Borneo and Sumatra.